Microsomal prostaglandin E2 synthase-1 and its inhibitors: Molecular mechanisms and therapeutic significance. (January 2022) - Zhang, Yan-Yu; Yao, Yun-Da; Luo, Jin-Fang; Liu, Zhong-Qiu; Huang, Yu-Ming; Wu, Fei-Chi; Sun, Qin-Hua; Liu, Jian-Xin; Zhou, Hua
Abstract: Inflammation is closely linked to the abnormal phospholipid metabolism chain of cyclooxygenase-2/microsomal prostaglandin E2 synthase-1/prostaglandin E2 (COX-2/mPGES-1/PGE2 ). In clinical practice, non-steroidal anti-inflammatory drugs (NSAIDs) as upstream COX-2 enzyme activity inhibitors are widely used to block COX-2 cascade to relieve inflammatory response. However, NSAIDs could also cause cardiovascular and gastrointestinal side effects due to its inhibition on other prostaglandins generation. To avoid this, targeting downstream mPGES-1 instead of upstream COX is preferable to selectively block overexpressed PGE2 in inflammatory diseases. Some mPGES-1 inhibitor candidates including synthetic compounds, natural products and existing anti-inflammatory drugs have been proved to be effective in in vitro experiments. After 20 years of in-depth research on mPGES-1 and its inhibitors, ISC 27864 have completed phase II clinical trial. In this review, we intend to summarize mPGES-1 inhibitors focused on their inhibitory specificity with perspectives for future drug development. Graphical Abstract: ga1